2019
DOI: 10.14198/jhse.2020.154.11
|View full text |Cite
|
Sign up to set email alerts
|

An alternative to oxygen deficit as a way to quantify anaerobic contributions in running

Abstract: The purpose of this study was to determine if the sum of estimates of the phosphocreatine contribution and the glycolytic contribution (we refer to this sum as PCr+glycolysis) provides an alternative to oxygen deficit as a way to quantify the anaerobic contribution in running. Thirty university students performed three treadmill tests, each test at one speed individually selected for each participant; one test was terminated after 3 min, one after 7 min, and one at exhaustion (mean ± SD, 10.3 ± 0.4 min). Oxyge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
1
0
Order By: Relevance
“…This method has been shown to be capable of terminating the maximum accumulated oxygen deficit, with the advantage of breaking down the anaerobic contribution into its ATP-PCr component (based on the EPOCfast) and glycolytic components (based on the conversion of blood lactate accumulation to oxygen equivalent) [ 56 ]. Its use and validity have been reported in running [ 57 , 58 , 59 ], and cycling [ 60 , 61 ], including high-intensity interval exercise [ 62 ].…”
Section: Energy Systems’ Contributions In Combat Sportsmentioning
confidence: 99%
“…This method has been shown to be capable of terminating the maximum accumulated oxygen deficit, with the advantage of breaking down the anaerobic contribution into its ATP-PCr component (based on the EPOCfast) and glycolytic components (based on the conversion of blood lactate accumulation to oxygen equivalent) [ 56 ]. Its use and validity have been reported in running [ 57 , 58 , 59 ], and cycling [ 60 , 61 ], including high-intensity interval exercise [ 62 ].…”
Section: Energy Systems’ Contributions In Combat Sportsmentioning
confidence: 99%
“…The estimated sum of PCr and glycolytic contribution generates a measure of total anaerobic contribution. Researchers have reported that oxygen deficit and PCr + glycolysis did not differ, and were highly correlated (Bertuzzi et al, 2010;Urso et al, 2010;Hill et al, 2020;Valenzuela et al, 2020). In the present study, we were not able to confirm the validity of the PCr+glycolysis measure in the normoxia condition.…”
Section: Anaerobic Contribution During Severe-intensity Exercisementioning
confidence: 99%